MECHANICAL PROPERTIES AND FRACTURE PREDICTION OF CONCRETES CONTAINING OIL PALM SHELL AND EXPANDED CLAY FOR FULL REPLACEMENT OF CONVENTIONAL AGGREGATES - Tan, Wei Li; Lee, Yeong Huei; Tan, Cher Siang; Lee, Yee Yong; Kueh, Ahmad Beng Hong (Penerbit UTM Press, 2022)
In order to reduce the continual depletion and exploitation of natural resources, this paper examines the mechanical properties and fracture prediction of sustainable lightweight aggregates concretes comprising agro-industrial waste or/and artificial aggregate, considering a full replacement of conventional coarse aggregate. The fresh and hardened properties are examined, from which three out of the five design mixes can achieve structural concrete specifications. It is observed that compression, tensile, and flexural strengths of the mixes exhibit a similar behaviour trend, as relatively higher values can be obtained from homogenous coarse aggregates compared to heterogeneous aggregates for different proportions of oil palm shell (OPS) and expanded clay replacement. The experimental results show compression strength of 13 to 32 MPa, splitting tensile strength of 1.32 to 2.97 MPa and flexural strength of 1.67 to 5.24 MPa for the investigated mixes at concrete age of 28-day. Most of the mixes are able to achieve structural use. Amongst the mixes, those containing expanded clay lower the corresponding sorptivity values. Although statistics prove that the prediction models of tensile and flexural strengths can represent existing experimental findings, further investigations are recommended for a better properties forecasting of lightweight aggregate concrete containing OPS and expanded clay.